The Effect of Filler ER5356 on Weld Metal Structure of 6061 Aluminium Alloy by Metal Inert Gas (MIG) - M., Ishak; Nur Fakhriah, Mohd Noordin; Ahmad Syazwan, Kamil Razali; L. H., Shah (Penerbit Universiti Malaysia Pahang, 2015)
Weldability can be defines as the ability of a material to be welded under imposed conditios. Good weldability of aluminiums alloys leads to have wide applicatins in marines, aircraft construction, aerospace and automobile industries. In this study, 6061 aluminium alloys will be joined by using automatic metal inert gas (MIG) welding machine. The filler metal used is ER5356 and ER4043. ER5356 filler contains 5.5% of magnesium and ER4043 filler contains 6% of silicon. The objectives of this research are to study the consequence of filler metal on mechanical properties of 6061 aluminium alloys.